The Impact of Carbon Disclosure on Firm Value with Foreign Ownership as A Moderating Variable - Muhammad, Gazani Izmar; Aryani, Y. Anni (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2021)
The purpose of the study is to analyze the effect of carbon disclosure on firm value and examine the moderation effect of foreign ownership. This study used all of the companies listed on the Indonesia Stock Exchange (BEI) between 2016 and 2018 as the population and employed a purposive sampling method to determine 194 companies as the final data observation. The data were collected from annual report and sustainability report released by the sample companies and analyzed using Moderated Regression Analysis (MRA). The result shows that carbon disclosure negatively affects firm value, while, foreign ownership significantly moderates the relationship between both variables.